Are the Recommended Criteria for Clinically Insignificant Prostate Cancer Applicable to 12-core Prostate Biopsy Scheme? A Multicentre Study of Urooncology Association, Turkey - Celik, Serdar; Kizilay, Fuat; Yorukoglu, Kutsal; Ozen, Haluk; Akdogan, Bulent; Izol, Volkan; Bayazit, Yildirim; Aslan, Guven; Sozen, Sinan; Baltaci, Sumer; Muezzinoglu, Talha; Narter, Fehmi; et al. (GALENOS PUBL HOUSE, 2021)
Objective: The aim of this study is to investigate the relevance of the Epstein criteria for the 12-core transrectal prostate biopsy (TRUS-Bx) scheme with the evaluation of clinicopathologic data recorded in the Urologic Cancer Database - Prostate (UroCaD-P), Urooncology Association, Turkey (UOAT). Materials and Methods: Patients with detailed pathological 12-core TRUS-Bx data for each biopsy core and who underwent RP due to PCa were included in this study. A total of 1167 patients from seven different centres were analysed. TRUS-Bx pathological findings were separately evaluated in the areas matching the sextant biopsy (6-core paramedian-lateral) scheme and in all 12-core biopsy areas (12-core biopsy scheme). Overall detection rates of PCa and ratios of clinically significant (sPCa) and insignificant PCa (insPCa) after RP were defined and compared between the biopsy schemes. Biopsy findings, according to the Epstein criteria, were also compared between the two schemes. A model for each biopsy scheme was created, including the Epstein criteria and additional biopsy findings using logistic regression analysis to predict clinically sPCa after RP. Results: There was a high correlation for the prediction of clinically insPCa between the two biopsy schemes in the same population. However, 7.3\% of PCa could not be diagnosed in the 6-core TRUS-Bx scheme. Also, 69.4\% of these had clinically sPCa according to the Epstein criteria in 12-core TRUS-Bx scheme and 51.8\% of these were clinically sPCa after RP. The presence of perineural invasion (PNI) in 12-core biopsy was also significant regarding predicting sPCa (p<0.001). Conclusion: The Epstein criteria in 12-core prostate biopsy provide a better prediction of clinically sPCa than the 6-core biopsy scheme. Biopsy PNI findings appeared to improve the effectiveness of 12-core prostate biopsy, in addition to the Epstein criteria.
Keywords: Prostate cancer; radical prostatectomy; clinically insignificant prostate cancer; Epstein criteria; 12-core prostate biopsy scheme